A rare case of small bowel obstruction secondary to ovarian torsion in an IVF pregnancy. (15th February 2013) - Lazaridis, Alexandros; Maclaran, Kate; Behar, Nebil; Narayanan, Priya
Abstract : A 39- year-old woman, who conceived following in vitro fertilisation (IVF) treatment, presented at 12 weeks gestation with symptoms of ovarian hyperstimulation syndrome (OHSS), abdominal pain, vomiting and diarrhoea. Subsequent investigations found small bowel obstruction secondary to ovarian torsion. Surgical management to remove a necrotic ovary and fallopian tube led to a good recovery from the acute illness. A postoperative ultrasound scan confirmed a viable pregnancy and the patient was discharged. Her case demonstrates a rare complication of OHSS and ovarian torsion leading to small bowel obstruction.